Method for reducing rubber crack propagation rate and tire
By adjusting the vulcanizing agent ratio according to the maximum tear energy and adding organic polysulfide to the sulfur to form a composite cross-linked network structure, the problem of excessive tire rubber crack expansion rate is solved and the service life of the tire is improved.
Patent Information
- Application Number
- CN202411942370.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, sulfur is used as the vulcanizing agent for rubber, which leads to the expansion rate of cracks that are too large when the tear energy of the tire rubber increases, the experience of use is poor, and the service life is short.
By obtaining the maximum tear energy in the application scenario, according to the maximum tearing energy can determine the amount of organic polysulfide and sulfur in the sulfur, mix the vulcanizer and the raw materials to obtain the target rubber material to form more stable and intensity more intensity. High composite network structure.
The extension rate of rubber cracks is reduced, the fracture and stretching strength and tear strength of the tire rubber are improved, and the service life is prolonged.
Smart Images

Figure CN119350732A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of tire rubber technology, and in particular to a method for reducing the growth rate of rubber cracks and a tire. Background Art
[0002] Natural rubber (NR) is widely used in shock absorbers, medical devices, tires and other industries due to its unique high elasticity and mechanical strength. However, there are initial defects in rubber and its products. These defects gradually develop into small cracks under the action of high-intensity impact and cyclic loads, and then expand, eventually leading to local damage or even complete failure of the product. The fatigue properties of rubber directly affect the durability of tires, so studying the fatigue properties of natural rubber is of great significance to improving the safety of tires and extending their service life.
[0003] Studies have shown that the crack initiation and propagation behavior of NR is not only affected by external mechanical loads (such as strength and strain ratio) and environmental conditions (such as temperature), but is also closely related to the material formulation (matrix and filler) and cross-linking structure (density and type). Among them, the higher the cross-linking density, the better the mechanical properties of the material, but excessive cross-linking will cause the material to become hard, affecting its elasticity and ductility.
[0004] In the preparation of automobile tires, rubber material is the main material. During the use of the tire, the tearing energy borne by the tire rubber is the main reason for the cracks in the tire rubber. In the prior art, sulfur is often used as a common vulcanizing agent for rubber during the tire production process. However, in the tires prepared by this method, after the tire rubber cracks due to excessive tearing energy, as the tearing energy increases, the crack expansion rate is too large, the crack expands too quickly, the use experience is poor, and the service life is short. Summary of the invention
[0005] The purpose of the present application is to provide a method for reducing the crack growth rate of rubber, so as to alleviate the technical problem that sulfur is used as a common vulcanizing agent for rubber in the prior art, resulting in excessive crack growth rate and excessive growth after cracks are generated in tire rubber.
[0006] In a first aspect, an embodiment of the present invention provides a method for reducing a crack growth rate of rubber, the method comprising: Obtain the maximum tearing energy in the application scenario; According to the maximum tearing energy, determine the amount of organic polysulfide and sulfur added in the vulcanizing agent; Mixing the vulcanizing agent with the raw materials to obtain the target rubber material; In combination with the first aspect, an embodiment of the present invention provides a first possible implementation manner of the first aspect, wherein the step of determining the amount of organic polysulfide to be added according to the maximum tearing energy comprises: If the maximum tear energy is less than or equal to 347 J / ㎡, the amount of organic polysulfide in the vulcanizing agent is 0; If the maximum tearing energy is greater than 347 J / ㎡, the amount of organic polysulfide added in the vulcanizing agent is greater than 0.
[0007] In combination with the first aspect, an embodiment of the present invention provides a first possible implementation method of the first aspect, where if the maximum tear energy is greater than 347 J / ㎡, the step of adding an amount of organic polysulfide in the vulcanizing agent greater than 0 comprises: If the maximum tear energy is less than or equal to 370 J / ㎡, the amount of organic polysulfide and sulfur added in the vulcanizing agent is greater than 0; If the maximum tear energy is greater than 370 J / ㎡, the amount of sulfur added in the vulcanizing agent is 0.
[0008] In combination with the first aspect, an embodiment of the present invention provides a first possible implementation method of the first aspect, if the maximum tear energy is less than or equal to 370 J / ㎡, the addition amount of organic polysulfide and sulfur in the vulcanizing agent is greater than 0, comprising: The weight ratio of sulfur to organic polysulfide is 1:2-1:5.
[0009] In combination with the first aspect, the embodiment of the present invention provides a first possible implementation of the first aspect, wherein the step of mixing a vulcanizing agent with a raw material to obtain a target rubber material comprises: The raw materials include: natural rubber, carbon black, carbon black coupling agent, accelerator, antioxidant, stearic acid and zinc oxide.
[0010] In combination with the first aspect, the embodiment of the present invention provides a first possible implementation of the first aspect, wherein the sulfur content of the sulfur is 60%-82%; The sulfur content of organic sulfur compounds is 25%-40%.
[0011] In a second aspect, an embodiment of the present invention provides a tire, comprising: The rubber material is made by the method for reducing the rubber crack growth rate provided by the first aspect.
[0012] The embodiments of the present invention bring the following beneficial effects: The present invention provides a method for reducing the crack growth rate of rubber, the method comprising: obtaining the maximum tearing energy in an application scenario; determining the addition amount of organic polysulfide and sulfur in a vulcanizing agent according to the maximum tearing energy; mixing the vulcanizing agent with raw materials to obtain a target rubber material.
[0013] Specifically, after obtaining the maximum tear energy in the application scenario, the present application selectively adjusts the ratio of the vulcanizer according to the maximum tear energy. When the maximum tear energy is large, an organic polysulfide is added to the sulfur. The organic polysulfide contains multiple thioalkyl chain segments. During the vulcanization process, the flexible alkyl chains can be connected to the rubber macromolecules to form a more stable and stronger composite cross-linked network structure, thereby improving the tensile strength and tear strength of the tire rubber, so that when cracks appear in the tire rubber, the crack propagation rate can be reduced when subjected to a large tear energy, thereby extending the service life.
[0014] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description, claims and drawings.
[0015] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0017] Figure 1 A flow chart of a method for reducing a rubber crack growth rate provided in Example 1 of the present application; Figure 2 A schematic diagram of the crack growth rates of NR-S, NR-S&PSO and NR-PSO provided in Example 1 of the present application; Figure 3 for Figure 2 Enlarged view of point A in the middle. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.
[0019] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0020] In order to facilitate the understanding of this embodiment, the application scenarios and design concepts of the embodiments of the present application are briefly introduced below.
[0021] Natural rubber (NR) exhibits its unique properties through different cross-linking reactions, and the type of cross-linking in the vulcanized rubber network structure is also an important factor affecting its performance. Vulcanization bonds can be divided into single sulfur bonds, disulfide bonds and polysulfide bonds, and the number and proportion of bond types have a significant impact on the performance of vulcanized rubber.
[0022] Studies have shown that in common vulcanization systems, the cross-linked network and polysulfide bonds in NR composites are key factors in reducing the crack growth rate. In the effect of cross-linking type on the fatigue crack growth behavior of filled natural rubber, the relative number of polysulfide bonds and monosulfide bonds was controlled by changing the ratio of sulfur to accelerator. It was found that when the cross-linking density was the same, the material with more polysulfide bonds had the best fatigue resistance. Compared with monosulfide bonds and disulfide bonds, polysulfide bonds have lower bond energy and can deform like elastic chains to dissipate energy and avoid strain-induced crystallization. Generally, vulcanized rubber with more monosulfide bonds has better physical properties and heat and aging resistance, while vulcanized rubber with more polysulfide bonds has good fatigue resistance, but due to its small bond energy, it is easily damaged by oxygen attack and has poor heat and aging resistance. Therefore, the performance of the vulcanized rubber can be adjusted by adjusting the cross-linking structure and type according to actual needs, among which the selection of vulcanizing agent is the key to building a cross-linked network.
[0023] Sulfur is a commonly used vulcanizing agent for rubber. The physical and mechanical properties and fatigue resistance of natural rubber can be adjusted by adjusting the ratio of accelerator to sulfur. However, the formation of the cross-linked network formed by it is easily affected by other fillers, such as the dispersibility of zinc oxide, which generates various vulcanization bonds, resulting in a high degree of heterogeneity (heterogeneity) in the cross-linked network and mixed components, which will significantly affect the mechanical properties of the vulcanized rubber. The sulfur donor vulcanization formula system does not contain elemental sulfur, which can effectively avoid this problem. In addition, the sulfur donor can partially or completely replace sulfur, dissociate active sulfur at the vulcanization temperature, and make the proportion of single sulfur bonds, disulfide bonds and polysulfide bonds more reasonable, thereby constructing a cross-linked network structure of vulcanized rubber with both static and dynamic mechanical properties and heat-oxidative aging resistance.
[0024] The fatigue crack growth rate (FCG) of rubber materials is an important factor affecting the fatigue durability of rubber products. Relevant studies have shown that organic polysulfides (PSO) can form a high-strength composite cross-linked network structure with rubber molecular chains, increase the polysulfide content in rubber, and thus reduce the crack growth rate of the material. 2 When compared with NR-S (rubber material prepared with sulfur as vulcanizing agent), NR-PSO (rubber material prepared with organic polysulfide as vulcanizing agent) has a crack growth rate reduced by about 80.9%, and a tear strength increased by about 55%. The greater the tear energy, the more obvious the effect of PSO in reducing the crack growth rate. It was also found that the more PSO in the material, the greater its crosslinking density, the more polysulfide bonds, and the smaller the crack growth rate.
[0025] The rubber material in tires is often subjected to high-intensity impacts and cyclic loads. Initial defects gradually develop into fine cracks, which then expand and directly lead to local damage and eventual failure of the product. The fatigue properties of rubber directly affect the durability of tires. Therefore, studying the fatigue properties of natural rubber is of great significance to improving the safety of tires and extending their service life.
[0026] Embodiment 1 This embodiment provides a method for reducing the crack growth rate of rubber. Figure 1 , the method specifically includes: S100, obtaining the maximum tearing energy in the application scenario.
[0027] S200, determining the amount of organic polysulfide and sulfur added in the vulcanizing agent based on the maximum tearing energy.
[0028] S300, mixing the vulcanizing agent with the raw materials to obtain the target rubber material.
[0029] Specifically, after obtaining the maximum tear energy in the application scenario, in this embodiment, the ratio of the vulcanizing agent is selectively adjusted according to the maximum tear energy. When the maximum tear energy is large, organic polysulfide is added to sulfur. The organic polysulfide contains multiple alkyl sulfide segments. During the vulcanization process, the flexible alkyl chains can be connected to the rubber macromolecules to form a more stable and stronger composite cross-linked network structure, thereby improving the tensile strength and tear strength of the tire rubber, so that when cracks appear in the tire rubber, the crack propagation rate can be reduced when the tire rubber is subjected to a large tear energy, thereby extending the service life.
[0030] Wherein, step S200, the step of determining the amount of organic polysulfide to be added according to the maximum tearing energy, comprises: S110, if the maximum tear energy is less than or equal to 347 J / ㎡, the amount of organic polysulfide in the vulcanizing agent is 0.
[0031] S120, if the maximum tear energy is greater than 347 J / ㎡, the amount of organic polysulfide added in the vulcanizing agent is greater than 0.
[0032] See also Figure 2 , Figure 3 It can be seen that when the maximum tear energy is less than 347 J / ㎡, the crack growth rate of NR-S is the smallest, and the crack growth rates of NR-S&PSO (rubber material prepared by combining organic polysulfide and sulfur as vulcanizing agent) and NR-PSO are greater than that of NR-S. Therefore, when the maximum tear energy is less than or equal to 347 J / ㎡, sulfur is used as a vulcanizing agent to prepare the rubber material, and the crack growth rate of the obtained rubber material is better when the maximum tear energy is less than 347 J / ㎡.
[0033] Furthermore, step S120, if the maximum tearing energy is greater than 347 J / ㎡, the amount of organic polysulfide added to the vulcanizing agent is greater than 0, comprises: S121, if the maximum tear energy is less than or equal to 370 J / ㎡, the addition amount of organic polysulfide and sulfur in the vulcanizing agent is greater than 0.
[0034] S122, if the maximum tear energy is greater than 370 J / ㎡, the amount of sulfur added in the vulcanizing agent is 0.
[0035] Please refer again Figure 3 It can be seen that when the tear energy is greater than 370 J / ㎡, the crack growth rate of NR-PSO is the smallest, followed by NR-S&PSO, and the crack growth rate of NR-S is the largest. Therefore, when the tear energy is greater than 347 J / ㎡ and less than 370 J / ㎡, the crack diffusion rate of the rubber material prepared by using sulfur and PSO as a vulcanizing agent is small. Similarly, when the tear energy is greater than 370 J / ㎡, the crack growth rate of the rubber material prepared by using PSO as a vulcanizing agent is small.
[0036] Specifically, in this embodiment, in step S121, if the maximum tear energy is less than or equal to 370 J / ㎡, the addition amount of organic polysulfide and sulfur in the vulcanizing agent is greater than 0, the step includes: The weight ratio of sulfur to organic polysulfide is 1:2-1:5.
[0037] Specifically, in this embodiment, the ratio of sulfur to organic polysulfide is 1.2:3.25. The vulcanizing agent formed under this ratio can achieve a relatively balanced effect. In the range of greater than 347 J / ㎡ and less than 370 J / ㎡, the crack growth rate is relatively small.
[0038] In this embodiment, S300, in the step of mixing the vulcanizing agent with the raw materials to obtain the target rubber material, the raw materials include: natural rubber, carbon black, carbon black coupling agent, accelerator, antioxidant, stearic acid and zinc oxide.
[0039] Among them, each raw material is added in a weight ratio. For example, under the condition that the addition amount of natural rubber is 100, the addition range of carbon black should be 30-50, the addition range of carbon black coupling agent should be 0.5-1.5, the addition range of accelerator should be 0.7-1.5, the addition range of antioxidant should be 0.5-1.5, the addition range of stearic acid should be 0.9-3, and the addition range of zinc oxide should be 1-5.
[0040] As shown in Table 1, specifically, the weight ratio of natural rubber, carbon black, carbon black coupling agent, accelerator, antioxidant, stearic acid and zinc oxide in the raw materials of this embodiment is 100:46.5:1:1.3:1:2:4.
[0041] Table 1 shows the raw material ratio (phr) of natural rubber composite materials.
[0042]
[0043] (Note: In Table 1, the total pure sulfur content of NR-S, NR-S&PSO and NR-PSO is the same) Among them, the number of PSO in NR-PSO, NR-PSO-3.25, NR-PSO-4.7 and NR-PSO-7.8 are 6.25, 3.25, 4.7 and 7.8 respectively.
[0044] In addition, step S300, mixing the vulcanizing agent with the raw material to obtain the target rubber material, comprises: S310, plasticizing the raw rubber to obtain plasticized rubber.
[0045] S320, mixing plasticized rubber, carbon black, carbon black coupling agent, accelerator, antioxidant, stearic acid and zinc oxide in one stage to obtain a masterbatch.
[0046] S330, the first-stage masterbatch, the vulcanizing agent and the accelerator are mixed in two stages to obtain the final mixed rubber.
[0047] S340, vulcanizing the final rubber mixture in a vulcanization temperature and pressure environment to obtain a target rubber material.
[0048] Specifically, in S310, in this embodiment, raw rubber is put into an internal mixer, the speed is limited to 30 rpm / min, the top bolt is pressed down, and when the temperature reaches 130° C., the rubber is discharged to obtain plasticized rubber. The plasticized rubber is then mixed twice and vulcanized to obtain the target rubber material.
[0049] In this embodiment, step S320, mixing plasticized rubber, carbon black, carbon black coupling agent, accelerator, antioxidant, stearic acid and zinc oxide to obtain a masterbatch, includes: The kneading was continued at a rotation speed of 25 rpm / min until the temperature reached 130°C and the kneading was stopped.
[0050] The temperature was lowered to 100°C and then kneaded at a rotation speed of 35 rpm / min to 130°C.
[0051] Stop mixing and discharge the rubber to obtain a masterbatch.
[0052] Specifically, in this embodiment, after obtaining the plasticized rubber through S310, the plasticized rubber, carbon black and other fine materials are put into the internal mixer, the initial speed is 25 rpm / min, and the mixing is about 90 seconds. When the temperature reaches 130°C, the top bolt is raised and the carbon black fine materials are cleaned. When the temperature drops to 100°C, the top bolt is pressed down again, and the speed is increased to 35 rpm / min. When the temperature rises to 130°C, the speed is increased to 60 rpm / min, and the glue is discharged when the temperature rises to 150°C, thereby obtaining a masterbatch.
[0053] In addition, in step S340 of this embodiment, a section of masterbatch, vulcanizer and accelerator are added to the mixing mill, a total of three cuts are made, and after three triangular packages and two long strips are made, the roller distance is adjusted to 2 mm, and a thin sheet is produced to obtain the final mixed rubber.
[0054] In this embodiment, step S340, the step of placing the final rubber mixture in a vulcanization temperature and pressure environment for vulcanization to obtain the target rubber material, includes: The vulcanization temperature and pressure environment is 150°C, 10MPa, and the vulcanization time is 30 minutes.
[0055] Specifically, after the final rubber mix is left for a certain period of time, the present embodiment uses a flat vulcanizer to vulcanize the final rubber mix for 30 minutes at a temperature of 150° C. and a pressure of 10 MPa to form a target rubber material.
[0056] It should be noted that the sulfur content of the sulfur used in the vulcanizing agent should be 60%-82%. Correspondingly, the sulfur content of the organic polysulfide used in the vulcanizing agent should be 25%-40%.
[0057] Sulfur and organic polysulfide with a sulfur content within this range can achieve the technical effects of the above embodiments.
[0058] In this embodiment, the sulfur content of the sulfur used in the vulcanizing agent is specifically 80%, and the sulfur content of the organic sulfur compound used in the vulcanizing agent is specifically 32%.
[0059] Embodiment 2 This embodiment provides a tire, including a rubber material, which is made by the method for reducing the rubber crack growth rate provided in the first embodiment.
[0060] Furthermore, it should be noted that the tire in this embodiment includes multiple parts. Different rubber materials can be used to bond the tire according to the maximum tearing energy that each part can withstand. The rubber materials used in each part of the tire can be the same material or different materials, so that each part of the tire can have good tearing strength.
[0061] Based on the above test results, it is found that increasing the number of PSO can reduce the crack growth rate of NR composite materials, and the greater the tearing energy, the more obvious the effect.
[0062] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0063] In the description of the present application, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc. indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, or the positions or positional relationships in which the product of the application is usually placed when in use. They are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific position, be constructed and operated in a specific position, and therefore cannot be understood as a limitation on the present application. In addition, the terms "first", "second", "third", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.
[0064] In addition, the terms "horizontal", "vertical", "overhanging" and the like do not mean that the components are required to be absolutely horizontal or overhanging, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", and does not mean that the structure must be completely horizontal, but can be slightly tilted.
[0065] In the description of this application, it should also be noted that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for reducing the crack growth rate of rubber, characterized in that: include: Obtain the maximum tearing energy in the application scenario; According to the maximum tearing energy, determining the addition amount of the organic polysulfide and the addition amount of the sulfur in the vulcanizing agent; The vulcanizing agent is mixed with the raw materials to produce rubber, thereby obtaining the target rubber material.
2. The method according to claim 1, characterized in that The step of determining the amount of the organic polysulfide to be added according to the maximum tearing energy comprises: If the maximum tear energy is less than or equal to 347 J / ㎡, the amount of the organic polysulfide in the vulcanizing agent is 0; If the maximum tear energy is greater than 347 J / ㎡, the added amount of the organic polysulfide in the vulcanizing agent is greater than 0.
3. The method according to claim 2, characterized in that The step of adding an amount of the organic polysulfide in the vulcanizing agent greater than 0 if the maximum tear energy is greater than 347 J / ㎡ comprises: If the maximum tear energy is less than or equal to 370 J / ㎡, the added amounts of the organic polysulfide and the sulfur in the vulcanizing agent are both greater than 0; If the maximum tear energy is greater than 370 J / ㎡, the amount of sulfur added in the vulcanizing agent is 0.
4. The method according to claim 3, characterized in that The step of: if the maximum tear energy is less than or equal to 370 J / ㎡, the addition amount of the organic polysulfide and the sulfur in the vulcanizing agent is greater than 0, comprises: The weight ratio of the sulfur to the organic polysulfide is 1:2-1:
5.
5. The method according to claim 1, characterized in that The step of mixing the vulcanizing agent with the raw material to obtain the target rubber material comprises: The raw materials include natural rubber, carbon black, carbon black coupling agent, accelerator, antioxidant, stearic acid and zinc oxide.
6. The method according to any one of claims 1 to 5, characterized in that The sulfur content of the sulfur is 60%-82%; The sulfur content of the organic polysulfide is 25%-40%.
7. A tire, characterized in that: include: A rubber material made by the method for reducing the crack growth rate of rubber according to any one of claims 1 to 6.
Citation Information
Patent Citations
High-fatigue-resistance rubber composition for tires as well as preparation method and application of high-fatigue-resistance rubber composition
CN114854110A
Apex rubber composition with stable modulus, mixing method and tire
CN116987329A
Rubber composition as well as preparation method and application thereof
CN118126421A
Sealing composition
RU2270226C1
Cited By
Construction method of crack growth rate model of spliced rubber
CN120068464A
Rubber fatigue crack growth rate prediction method and system, storage medium and program product
CN121090313A
A method, system, storage medium, and program product for predicting rubber fatigue crack growth rate
CN121090313B